EXPLORING CUSTOMER SATISFACTION IN HOTEL RESTAURANTS: THE ROLE OF PERCEIVED VALUE AND THE MODERATING EFFECT OF COVID-19 FEAR - Donna, Lee; Mark, Kasa; Azizan, Yatim (Global Academic Excellence (M) Sdn Bhd (GAE), 2025)
This study examined how perceived value dimensions (physical environment, trust, corporate reputation, and price) influence customer satisfaction in hotel restaurants in Kuching, Malaysia. This study also explored the moderating role of COVID-19 fear on these relationships. Using data from 285 structured questionnaire responses, the findings reveal that all value dimensions are positively associated with customer satisfaction. Additionally, it was suggested that COVID-19 fear is positively related to customer satisfaction and significantly moderates the effects of the physical environment and corporate reputation, but not trust or price, on satisfaction. This research integrates perceived value theory with the Stimulus–Organism–Response (S-O-R) model to provide new insights into customer behaviour in the post-pandemic hospitality context. The results offer actionable implications for hotel restaurant managers seeking to rebuild consumer trust, optimise service value, and adapt to customers’ heightened health and safety concerns in the wake of COVID-19.